Pengaruh Ukuran Perusahaan dan Pertumbuhan Penjualan Terhadap Struktur Modal dengan Profitabilitas Sebagai Variabel Moderasi - Riska Melita; Lamria Simamora; Rini Oktavia; Oktobria Y. Asi; Agus Kubertein; Septa Soraida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to examine the influence of company size and sales growth on capital structure with profitability as a moderating variable (in IDX30 index companies for the 2019-2022 period). The research method used in this research is quantitative research and uses secondary data collection techniques in the form of annual reports. The sample in this study was selected using a purposive sampling method and a sample of 15 IDX30 companies was obtained that met the sample criteria. The data analysis method used is multiple linear regression analysis and Moderated Regression Analysis. The results of this research indicate that company size has an effect on capital structure. Meanwhile, sales growth has no effect on capital structure. Moderating profitability can strengthen the influence of company size on capital structure. Meanwhile, moderate profitability can weaken the influence of sales growth on capital structure.